If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6xy + -7b = 0 Reorder the terms: -7b + 2x + 6xy = 0 Solving -7b + 2x + 6xy = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2x' to each side of the equation. -7b + 2x + -2x + 6xy = 0 + -2x Combine like terms: 2x + -2x = 0 -7b + 0 + 6xy = 0 + -2x -7b + 6xy = 0 + -2x Remove the zero: -7b + 6xy = -2x Add '-6xy' to each side of the equation. -7b + 6xy + -6xy = -2x + -6xy Combine like terms: 6xy + -6xy = 0 -7b + 0 = -2x + -6xy -7b = -2x + -6xy Divide each side by '-7'. b = 0.2857142857x + 0.8571428571xy Simplifying b = 0.2857142857x + 0.8571428571xy
| 9u^3+27u^2+18u=0 | | 0.11*0.33= | | 1.6*0.05= | | 15v^2+17v-42=0 | | 9y^2-15y+5=y-9 | | 3xy+y=15 | | T+-240=350 | | 2(x+6)=20 | | 4.8x+57.5=5.9-8.1x | | 90x^9+63x^8-48x^7=0 | | 65=1/2(x-115) | | 3p-(p+6)= | | 8+2y-6=7y+14-3y | | -(6y+2)-(-5y-4)=-4 | | 3(x^2-10x+16)=0 | | w^3x^7-w^3= | | 5x(7)=5x-8(6) | | 16(2x-9)=4(8x+5) | | 5x^2-14+8=0 | | 9+15z-2=8z+46-6z | | 2x(6)=3x-8(10) | | 31-61=5(x-3) | | 5x-8*7=5x*6 | | 8s+15s=69 | | 8s+15x=69 | | 5x-8(7)=5x(6) | | -10.9x=87.2 | | 3-2(n-4)=-1 | | 5(c+4)=5(c-2) | | -4(4b+1)+(17b-5)=0 | | 9e^5x=1035 | | 4.5q-2.7-5.6q=-2.1q-5.6 |